Strategy for Strengthening Confucian Religious Education Services Through Teacher Recruitment Policies in Bangka Belitung - Andreas Yudho Astono (AMUYA: JOURNAL OF MANAGEMENT, 2026)
The issue of suboptimal Confucian religious education services in the Bangka Belitung Islands Province is a critical concern that results in the neglect of students' constitutional rights. The core problem is rooted in a drastic imbalance between the number of students and the quantity of educators, exacerbated by low interest among prospective students due to career prospect uncertainty and the limited number of higher education institutions for Confucian studies. This paper aims to formulate strategic solutions to break the chain of teacher shortages through an integrative policy approach. The policy methodology employed is descriptive qualitative analysis, applying William N. Dunn’s policy evaluation framework. The analytical process involves comprehensive problem identification and the establishment of evaluation criteria—including effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness—followed by scoring various intervention options. The analysis concludes that a recruitment policy through an integrated service-bond scheme (ikatan dinas) is the most incisive step to simultaneously resolve upstream and downstream issues. The primary recommendation is the establishment of a Minister of Religious Affairs Regulation concerning service-bond patterns and the placement of graduates from Confucian religious higher education institutions. This policy is projected to provide career certainty for students, ensure competency linearity, and stabilize the teacher supply in critical regions through cross-sectoral coordination with national civil service authorities. The implementation of this recommendation is expected to transform religious study programs into high-value career paths while ensuring the sustainability of character education based on Confucian values in public schools, thereby guaranteeing social justice and religious moderation at the regional level sustainably